Effect of Uncaria rhynchophylla against Thioacetamide-Induced Acute Liver Injury in Rat. (14th September 2021) - Shin, Mi-Rae; Kim, Min Ju; Lee, Jin A; Roh, Seong-Soo
Abstract : Both oxidative stress (OS) and inflammation are two fundamental pathological processes of acute liver injury (ALI). The current work is to investigate the effect and possible mechanism of Uncaria rhynchophylla (UR) on thioacetamide- (TAA-) induced ALI in rats. UR (100 and 200 mg/kg) was orally administrated with TAA (200 mg/kg of bodyweight, intraperitoneal injection) for 3 consecutive days. ALI was confirmed using histological examination and the factors associated with OS and liver function activity measured in serum. Moreover, expressions of inflammation and collagen-related proteins were measured by the Western blot analysis. Myeloperoxidase (MPO), which mediates OS in the ALI control group, was manifested by a significant rise compared with the normal group. UR significantly reduced AST, ALT, and ammonia levels in serum. The nuclear factor- κ B (NF- κ B) activation induced by TAA led to increase both inflammatory mediators and cytokines. Whereas, UR administration remarkably suppressed such an overexpression. UR supplementation improved matrix metalloproteinases (MMPs) such as MMP-1, -2, and -8. In contrast, tissue inhibitors of metalloproteinases- (TIMP-) 1 level increased significantly by UR treatment. In addition, the histopathological analysis showed that the liver tissue lesions were improved obviously by UR treatment. UR may ameliorate the effects of TAA-induced ALI in rats by suppressing both OS through MPO activation and proinflammatory factors through NF- κ B activation. In conclusion, UR exhibited a potent hepatoprotective effect on ALI through the suppression of OS.